A Novel Thioredoxin-Like Protein of Babesia microti Involved in Parasite Pathogenicity - Piao, Xianyu; Ma, Yu; Liu, Shuai; Hou, Nan; Chen, Qijun (Frontiers in Cellular and Infection Microbiology, 2022)
Babesiosis poses a serious threat to immunocompromised individuals and the major etiological species of Babesia for human babesiosis is Babesia microti. Merozoites are a critical stage in the life cycle of Babesia microti. Several merozoite proteins have been demonstrated to play important roles in this process; however, most of the merozoite proteins of B. microti remain unknown. In the present study, we identified a novel merozoite protein of B. microti with similar structure to the thioredoxin (Trx)-like domain of the Trx family, which was named as B. microti Trx-like protein (BmTLP). Western blot assays demonstrated that this protein was expressed by B. microti during the erythrocytic infection process and its expression peaked on day 7 post-infection in vivo. Immunofluorescence assay further showed that this protein is mainly expressed in B. microti merozoites. BmTLP hold both heparin- and erythrocyte-binding properties, which are critical functions of invasion-related proteins. Immunization with recombinant BmTLP imparted significant protection against B. microti infection in mice. Taken together, these results suggest that the novel merozoite protein, BmTLP, is an important pathogenic molecule of B. microti and may be a possible target for the design of babesiosis control strategy.